Release kinetics of salbutamol sulphate from wax coated microcapsules and tableted microcapsules - Raghuvanshi R.S.; Tripathi K.P.; Jayaswal S.B.; Singh J. (My University, 2025)
Microcapsules of salbutamol sulphate were prepared using beeswax and car-nauba wax as coating materials. In vitro release kinetics were studied following the zero order, first order and Higuchi equations. Beeswax alone was not effective but beeswax and carnauba wax combinations were suitable in controlling the in vitro release of the drug. Microcapsules were compressed into tablets to get a controlled release oral dosage form. Release from tableted microcapsules was significantly more prolonged than the respective batches of the microcapsules. Best data fit with the highest correlation coefficient for the tableted microcapsules was obtained for first order. © 1992 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.